Black post-blackness the Black Arts Movement and twenty-first-century aesthetics - Crawford, Margo Natalie 1969- (University of Illinois Press, 2017)
A 2008 cover of The New Yorker featured a much-discussed Black Power parody of Michelle and Barack Obama. The image put a spotlight on how easy it is to flatten the Black Power movement as we imagine new types of blackness. Margo Natalie Crawford argues that we have misread the Black Arts Movement's call for blackness. We have failed to see the movement's anticipation of the "new black" and "post-black." Black Post-Blackness compares the black avant-garde of the 1960s and 1970s Black Arts Movement with the most innovative spins of twenty-first century black aesthetics. Crawford zooms in on the 1970s second wave of the Black Arts Movement and shows the connections between this final wave of the Black Arts movement and the early years of twenty-first century black aesthetics. She uncovers the circle of black post-blackness that pivots on the power of anticipation, abstraction, mixed media, the global South, satire, public interiority, and the fantastic
Keywords: Visuelle Kunst; Geschichte 2000-2016; Black arts movement; Schwarze; Literatur; USA; African-American literature and culture / 21st century; Black Arts movement / 21st century; Black nationalism